Minority stress theory applied to conception, pregnancy, and pregnancy loss: A qualitative study examining LGBTQ+ people's experiences. - Ashley Lacombe-Duncan; Nazanin Andalibi; Lee Roosevelt; Emma Weinstein-Levey (PLoS ONE, 2022)
Many lesbian, gay, bisexual, transgender (trans), queer, and other sexual and gender minority (LGBTQ+) people desire to conceive children. Yet, LGBTQ+ peoples' experiences are scant in reproductive health literature, particularly around pregnancy loss-a stigmatized and distressing pregnancy outcome. Informed by minority stress theory, this qualitative study aimed to explore the experiences of multi-level stigma and resilience among LGBTQ+ people in the context of conception, pregnancy, and loss. Seventeen semi-structured individual interviews (25-70 minutes) were conducted (2019) with a purposive sample of LGBTQ+ people in the United States (U.S.) who had experienced pregnancy loss (n = 14) or in an intimate partnership in which a pregnancy was lost (n = 3) in the last two years. Transcribed interviews were analyzed thematically. Participants described the profound sadness of pregnancy loss due to unique challenges of LGBTQ+ conception. Multiple types of stigma manifested at intrapersonal (e.g., anticipated sexual stigma upon disclosure), interpersonal (e.g., unsolicited advice about conception decisions), and structural levels (e.g., differential requirements to access conception compared to heterosexual/cisgender couples). Resilience was also seen individually (e.g., purposeful disclosure of conception, pregnancy, and loss), relationally (e.g., connecting with other LGBTQ+ community members), and collectively (e.g., creating/engaging in LGBTQ+-specific conception, pregnancy, and loss online spaces). LGBTQ+ people experience minority stressors of multi-level stigmatization throughout the pregnancy process, which limits their access to social support after experiencing pregnancy loss. However, individual, relational, and collective resilience strategies abound in response. Thus, minority stress theory can also be applied to recognize strengths-based and affirming approaches to reproductive healthcare for LGBTQ+ people.